FGF21 inhibits ferroptosis caused by mitochondrial damage to promote the repair of peripheral nerve injury - Yan, Yao; Ran, Xinyu; Zhou, Zihan; Gu, Yuting; Wang, Rendu; Qiu, Chuanqi; Sun, Yinuo; Wang, Jifeng; Xiao, Jian; Lu, Yingfeng; Wang, Jian (Frontiers in Pharmacology, 2024)
Introduction Ferroptosis is a new type of cell death characterized by lipid peroxidation and iron dependency, representing an emerging disease regulation mechanism. The limited understanding of ferroptosis in peripheral nerve injury (PNI) complicates the management of such injuries. Mitochondrial dysfunction, which contributes to ferroptosis, further exacerbates the challenges of peripheral nerve repair Methods In this study, we established an in vitro model of Schwann cells model treated with TBHP and an in vivo sciatic nerve crush injury model in rats. These models were used to investigate the effects of fibroblast growth factor 21 (FGF21) on PNI, both in vitro and in vivo, and to explore the potential mechanisms linking injury-induced ferroptosis and mitochondrial dysfunction. Results Our findings reveal that PNI triggers abnormal accumulation of lipid reactive oxygen species (ROS) and inactivates mitochondrial respiratory chain complex III, leading to mitochondrial dysfunction. This dysfunction catalyzes the oxidation of excessive polyunsaturated fatty acids, resulting in antioxidant imbalance and loss of ferroptosis suppressor protein 1 (FSP1), which drives lipid peroxidation. Additionally, irregular iron metabolism, defective mitophagy, and other factors contribute to the induction of ferroptosis. Importantly, we found that FGF21 attenuates the abnormal accumulation of lipid ROS, restores mitochondrial function, and suppresses ferroptosis, thus promoting PNI repair. Notably, glutathione peroxidase 4 (GPX4), a downstream target of nuclear factor E2-related factor 2 (Nrf2), and the ERK/Nrf2 pathway are involved in the regulation of ferroptosis by FGF21. Conclusion FGF21 promotes peripheral nerve repair by inhibiting ferroptosis caused by mitochondrial dysfunction. Therefore, targeting mitochondria and ferroptosis represents a promising therapeutic strategy for effective PNI repair.